HAYIM TAWIL, An Akkadian Lexical Companion for Biblical Hebrew: Etymological-Semantic and Idiomatic Equivalents with Supplement on Biblical Aramaic. Jersey City, NJ: Ktav Publishing House, 2009. Pp. xxiv + 503. ISBN 978–1–60280–114–1. USD 35,55 - Rostom Maderna, Santiago (2013)
Fil: Rostom Maderna, Santiago. Pontificia Universidad Católica Argentina; Argentina